Assessment Of Nurses’ Knowledge Towards Prevention Of Pressure Ulcer In Telafer General Hospital (Journal of Pharmaceutical Negative Results, 2023)
Background: Pressure ulcers are one of the top five patient hazards today, and they are a globally acknowledged problem with patient safety that may be avoided. More and more, the phrase "indicator of the quality of treatment provided by health care organizations" Methods: The Telafer General Hospital conducted a descriptive design study between December 2021 and March 2022. 100 nurses who worked in the medical ward, pediatric unit, cardio care unit, and surgical ward at Telafer General Hospital during the study period made up the study's sample. Results: The age range from 20 to 25 years represented by the majority of nurses (48%) was. In terms of gender, male nurses make up 64% of the nursing workforce, while female nurses make up 36%. Despite the fact that education level was a factor, the majority of nurses (48%) were high school graduates. In terms of years of experience, the majority of nurses (74%) had between 1 and 5 years under their belts. In terms of place of employment, a significant portion of nurses (32%) were employed in the heart care unit. Conclusion: We concluded from this analysis that nurses lacked a thorough understanding of pressure ulcer prophylaxis.